The Interaction Between Root Knot Nematode Meloidogyne incognita and the Vascular Wilt Fungi fusarium oxysporium f. sp. lycopersici - Mussa, Mohamed A.; Saeed, Mohamed A.; Ehwaeti, Mahmoud E. (Al-Mukhtar Journal of Sciences, 2002)
This study was conducted to investigate the interaction between the Root Knot causing Nematode Meloidogyne incognita and the wilt causing fungus Fusarium oxysporium f. sp. lycopersici on the tomato cultivates: Rio grande, Special back, and Rutgers, the study indicated that infection of tomato cultivars by the nematode increase their susceptibility to infection by the fungus. This susceptibilty was clearly notable on the tomato cultivars, Rutgers. The percent of infection was 5% in case of fungus alone, but in the combination between the fungus and nematodes it increased up to 14.8%. The present of the fungus decrease the number of galls and egg masses on all the tested cultivares, and it was clearly notable on the c.v. Rio grande were the average number of galls was 64.1 and the egg masses was 5.03 per gram roots in case of the infection by nematodes alone, and increased to 20.3 galls, 0.6 egg masses in case of fungus and nematodes.